Halal Research During COVID-19 Pandemic: A Bibliometric Analysis - Priantina, Anita; Mohd Sapian, Safeza; Syahnum, Melvina (AL-QARDH, 2023)
After the COVID-19 pandemic, there has been a worldwide increase in awareness of the concept of halal. During this crisis, the number of research papers published on Halal and COVID-19 has also increased, possibly due to the increased reliance on the internet. This study conducts a systematic review and bibliometric analysis of 156 relevant papers, using Google Scholar and Harzing Publish or Perish, to identify trends and provide future research directions in the field of halal studies. The result of Vosviewer shows that there are six clusters of keywords with a significant number of studies discussing halal tourism and halal food. Indonesia and Malaysia are frequently studied on this topic. Towards the end of the pandemic, the topic of halal tends to increase in certification issues.